Analyzing on The Impact of Celebrity Endorsements in Non-professional Fields on Brand Image - Wang, Shuye (Transactions on Economics, Business and Management Research, 2024)
Jia Ling, a renowned actress and director in China, showcased her pursuit of a healthy lifestyle over the course of a year during the preparation for the move “Yolo.” During the film’s promotional events, she frequently wore Lululemon’s clothing line. This summer, Lululemon officially announced Jia Ling as its brand ambassador. The study’s goal was to investigate how celebrity endorsements in non-professional fields influence brand image reshaping. This research uses Jia Ling’s appointment as Lululemon’s new brand ambassador as a case study, analyzing it through the lens of social identity theory and brand repositioning theory. The study discovered that celebrity endorsements in non-professional fields can effectively increase brand awareness and acceptance, enabling Lululemon to produce more environmentally friendly products. Furthermore, endorsements can influence brand image diversification and repositioning. At this point, Lululemon can cooperate with a Chinese local brand. Finally, Lululemon can enhance its emotional connection with consumers by choosing specific locations for brand events, thereby strengthening its relationship with potential customers.